2018
DOI: 10.5114/areh.2018.83389
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the correlations between the level of physical activity and sociodemographic factors, functional capabilities and cognitive capabilities of elderly persons from south-eastern Poland

Abstract: Introduction: Insufficient physical activity constitutes one of the most problematic issues in the contemporary society. Data show that seniors should take up physical activity as it considerably affects their health and quality of life. Material and method: The study included 76 individuals over 60 years of age who actively participated in social life (Senior Clubs, Country Housewives' Clubs, Folk groups) in southeastern Poland. The International Physical Activity Questionnaire (IPAQ), Timed Up and Go Test (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…This disability can cause early inability to work and loss of independence, as well as decreased psychophysical capabilities which can lead to reduced social participation. 3 The evidence confirmed that the total physical activity time in the elderly reduced above 35% after the COVID-19 pandemic. Regular physical exercise and/or activity play a significant role in preventing contrary health consequences.4,5 Close monitoring and rehabilitation intervention are necessary to ensure the well-being of older adults affected by COVID-19, elderly are highly recommended to exercise after COVID-19 recovery.…”
Section: Introductionmentioning
confidence: 57%
“…This disability can cause early inability to work and loss of independence, as well as decreased psychophysical capabilities which can lead to reduced social participation. 3 The evidence confirmed that the total physical activity time in the elderly reduced above 35% after the COVID-19 pandemic. Regular physical exercise and/or activity play a significant role in preventing contrary health consequences.4,5 Close monitoring and rehabilitation intervention are necessary to ensure the well-being of older adults affected by COVID-19, elderly are highly recommended to exercise after COVID-19 recovery.…”
Section: Introductionmentioning
confidence: 57%
“…Both cross-sectional and prospective studies have indicated the correlations between regular physical activity and reduced risk of dementia and deterioration of cognitive function (Chodzko-Zajko et al, 2009). Results of experimental studies suggest that regular physical exercise improves general cognitive function such as attention, memory or speed of information processing (Kelly et al, 2014;Voelcker-Rehage & Niemann, 2014;Chodzk-Zajko et al, 2009;Chapman et al, 2013;Eggenberger et al, 2016;Gonzalez-Palau et al, 2014;Szmul et al, 2018). Despite relatively numerous studies that have demonstrated the benefits of the cognitive area the researchers emphasize the need for further research (Brown et al, 2017;Young et al, 2015;Theocharidou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%